Theological Foundations in the Development of the Arabic Language Curriculum - Isop Syafei; Ade Arip Ardiansyah; Dadan Nugraha (UIN Sunan Gunung Djati Bandung, 2025)
This study explores the theological foundations in the development of the Arabic language curriculum as an integrative effort between Islamic values and contemporary educational needs. The Arabic language curriculum is not merely viewed as a linguistic instrument but also as a medium for character building, strengthening of Islamic faith (aqidah), and preservation of the Islamic scientific heritage. The aim of this study is to uncover theological dimensions that can serve as a basis for the planning, implementation, and evaluation of the Arabic language curriculum in Islamic educational institutions. This research employs a qualitative approach using a literature review method, critically examining primary and secondary sources such as the Qur’an, Hadith, Islamic educational literature, and curriculum documents. Data were collected through documentation and analyzed using a descriptive-analytical method. The results of the study reveal five main theological dimensions that can underpin the development of the Arabic language curriculum: monotheism (tawhid), revelation as a source of knowledge, worship (ibadah) as the goal of learning, Islamic education (tarbiyah Islamiyah) as a holistic educational process, and Islamic civilization as a historical and cultural framework. These findings emphasize the importance of integrating theological values in constructing an Arabic language curriculum that is not only academically functional but also spiritually transformative.